Spatial Construction In Visual Arts: Overlapped Space By Different Images, Dimensions, And Contexts - Feng, Hanping (2024)
The concept of "space" has gained widespread usage across many academic disciplines, including sociology, architecture, philosophy, mathematics, and the arts. Within pictorial art, the term "space" is commonly employed as a lens to comprehend various artistic concepts and individual works of art. Additionally, numerous artists utilise space as a subject matter in their artistic practice, creating unique artworks and contributing to advancing spatial themes and formulations in painting, either directly or indirectly. This study focuses mainly on overlapped space and its theoretical examination, leading to the creation of practical works. Specifically, this study reinforced and fulfilled the researcher's concepts by utilizing Edward Soja's theory of the 'Third Space'. In the process of the study, three separate series of artworks were gradually produced by Derrida's core concept of "Différance", which are the overlap of images, the overlap of different dimensional spaces, and the overlap of contexts respectively, the overall process will five steps, which are Identify research question, Review the literature and the practice, Design and conduct practice, Analyse and evaluate practice and Communicate and Disseminate Practice respectively, so that the various possibilities of overlapped space are analysed from multiple perspectives, that is, different disciplines.